Using of the Larval Morphology in Identification and Characteristic of some Species of Ladybird Beetles (Coleoptera: Coccinellidae). (Damascus University Journal of agriculture sciences, 2021)
This study was conducted in biological control studies and research center at Faculty of Agriculture/University of Damascus in 2015-2016 to morphologically identify the causal fungus of chalkbrood of honey bee. Infected samples were collected from different apiaries from Damascus and Latakia. Morphological description showed that Ascosphaera apisis the causal agent of chalkbrood disease in tested apiaries from Damascus and Latakia. Also, The result showed differences in average of ascoma diameter of latakia isolates (73.77µm) in comparison with Damascus isolates (89 µm), and in of Spore balls average of latakia isolates (14.43µm) in comparison with Damascus isolates (13.58 µm). Isolates from Latakia were more rapid in growth and sporulation in comparison with those from Damascus with significant difference at P= 0.01.
Keywords: chalkbrood; Ascosphaeraapis; Syria; honey bees